Antigenic Analysis of the Major Outer Membrane Protein of Chlamydia spp - Caldwell, Harlan D. (1982)
The major outer membrane proteins (MOMPs) of several Chlamydia trachomatis serotypes (B, D, G, H, and L2) and of the C. psittaci meningopneumonitis strain were purified by preparatory sodium dodecyl sulfate-(SDS)-polyacrylamide gel electrophoresis. The isolated SDS-polypeptide complexes, which varied in their apparent subunit molecular weights, were used as immunogens to raise hyperimmune rabbit antisera. The specificities of these antisera were determined both by rocket immunoelectrophoresis with the soluble SDS-polypeptide complex as antigen and by micro-immunofluorescence with whole organisms. By rocket immunoelectrophoresis, each of the soluble C. trachomatis MOMPs was immunologically related; however, no immunological cross-reactions occurred with the C. psittaci meningopneumonitis polypeptide, indicating that the MOMPs are antigenically distinct among members of these two chlamydial species. The same antisera were highly reactive with intact organisms by micro-immunfluorescence, demonstrating that at least some of the antibodies raised with SDS-polypeptide complexes reacted with native antigenic sites of these surface proteins. By micro-immunofluorescence, anti-MOMP sera remained species specific; but, unlike the results observed by rocket immunoelectrophoresis, distinct differences in the reactivity and specificity of these antisera were observed among C. trachomatis serotypes. C. trachomatis isolates were separated into two distinct serogroups on the basis of their reactivity with anti-MOMP sera. B complex organisms (B, Ba, D, E, F, G, K, L1, L2, and L3) all reacted strongly with anti-MOMP sera of the B, D, G, and L2 serotypes. In contrast, these same antisera were poorly reactive with the C complex serotypes A, C, H, I, and J. Anti-H MOMP serum was the most serospecific, since high-antibody titers were found only against the homologous H serotype organism. These findings indicate that MOMPs of different strains of C. trachomatis are antigenically complex and that antigenic heterogeneity exists among the surface-exposed portions of the protein.